Hubungan Orang Tua, Lingkungan Dan Guru Dalam Pendidikan Anak - laili mutafarrida (Sangkalemo : The Elementary School Teacher Education Journal, 2023)
The purpose of this study was to describe early childhood education and creativity in education at school and at home. A person's education begins when he is small and is important in a child's life. This study uses a type of qualitative research with a Library Research approach. Early childhood education starts at home accompanied by parents, parents are the main role models for a child, teachers are the successors of children's education at school after children receive education at home, and the environment is a place where children explore what is good and what is bad.